A Critical Analysis of Orientalist’s Views about Origin and Nature of Istihsan - Awan, Yasser Arafat (Journal of Islamic and Religious Studies, 2017)
Islamic Fiqh is the representative of legal aspect of Islam. It has been originated and established on direct teachings of Qur’an and Sunnah of the Holy Prophet Muhammad (SAW).These two sources are called primary sources of Islamic law. There are some supplementary sources to the primary sources; Istihsan (Juristic Preference) is one of these. Orinetalist’s studied and produced literature on Islamic law. Istihsan has also been discussed by them but they have different opinions about its origin and its role in Islamic law. In this article their opinions are being critically analyzed and the definition, role and types of Istihsan being presented according to Muslim’s viewpoint. This research concluded that the Goldziher, Joseph Schacht, MicDonald, David Pearl, and Benjamin Jokisch explanations about the establishment of Isti╒san are not correct.